Stacking nitrogen mitigation strategies for future pasture-based dairy farms: impacts on leaching and profit - Beukes, Pierre C.; Depree, Craig; Macintosh, Katrina A.; Silva-Villacorta, David (Frontiers in Animal Science, 2024)
Producers in New Zealand's pasture-based, seasonal dairy sector are striving to reduce nitrogen (N) losses to the environment whilst maintaining or increasing farm profitability. This study examined the cost-effectiveness of stacking different combinations of five N leaching mitigation strategies within the whole farm system; 1) reduced N fertilizer input, 2) off-paddock infrastructure, 3) recycling N by growing maize silage on a dedicated area on the farm using effluent as a fertilizer source followed by a catch-crop, 4) dietary salt supplementation to dilute urinary N, and 5) applying a nitrification inhibitor (NI) to slow the release of nitrate in the soil. The reference point (baseline) was a typical current dairy farm (CF) system in the Waikato region of New Zealand. We modelled four Future Farm scenarios by stacking mitigation strategies as follows: baseline plus reduced N fertilizer input, reduced stocking rate, and off-paddock infrastructure (FF); FF plus a dedicated maize block (FFP); FFP plus dietary salt (FFPS); and FFPS plus NI (FFPSNI). These systems were modelled using the Whole Farm Model coupled with the Urine Patch Framework, and APSIM models, using observed climate and economic input data over five consecutive years from 2013-2018. Relative to CF, the FF system achieved a N leaching reduction of 31% with a reduction in profit of 16%. The FFP system had a smaller N leaching reduction (22%), but the reduction in profit was smaller (11%). The fully stacked system (FFPSNI) demonstrated the largest leaching reduction of 33%, but also the largest profit reduction of 27%, compared with the CF. Stacking these five N mitigation strategies can achieve substantial N leaching reductions at the farm-scale. Including a dedicated, effluent-fertilized maize block followed by a catch-crop as part of the stack can reduce the negative impact on profitability but has a trade-off in N leaching. Farmers will have to weigh up these compromises between profit and leaching, considering risk factors not modelled here.